A PTPN11 allele encoding a catalytically impaired SHP2 protein in a patient with a Noonan syndrome phenotype - Edwards, Jonathan J. (2014)
The RASopathies are a relatively common group of phenotypically similar and genetically related autosomal dominant genetic syndromes caused by missense mutations affecting genes participating in the RAS/mitogen-activated protein kinase (MAPK) pathway that include Noonan syndrome (NS) and Noonan syndrome with multiple lentigines (NSML, formerly LEOPARD syndrome). NS and NSML can be difficult to differentiate during infancy, but the presence of multiple lentigines, café au lait spots, and specific cardiac defects facilitate the diagnosis. Furthermore, individual PTPN11 missense mutations are highly specific to each syndrome and engender opposite biochemical alterations on the function of SHP-2, the protein product of that gene. Here, we report on a 5-year-old male with two de novo PTPN11 mutations in cis, c.1471C>T (p.Pro491Ser) and c.1492C>T (p.Arg498Trp), which are associated with NS and NSML, respectively. This boy’s phenotype is intermediate between NS and NSML with facial dysmorphism, short stature, mild global developmental delay, pulmonic stenosis and deafness but absence of café au lait spots or lentigines. The double-mutant SHP-2 was found to be catalytically impaired. This raises the question of whether clinical differences between NS and NSML can be ascribed solely to the relative SHP-2 catalytic activity.